(untitled) (Jagannath University Journal of Arts, 2026)
Since ancient times, patgaan has been a medium through which the rural populace of Bangladesh has received education. At one time, patuas or pat artists in Bangladesh would earn their livelihood by performing patgaan while simultaneously providing folk education to the impoverished masses. The core elements of patachitra—illustration and music—are not merely blended seamlessly but also inevitably reflect the artists’ ambiguous religious stance, a subject that has intrigued researchers and critics from various perspectives. Our discussion centers on Gazir Pat. Through data, references, and field studies, we will explore the origins of pat and patachitra, the artistic conventions of patuas, their religious positioning, and the characteristics of patgaan to determine the multidimensional connections of Gazir Pat. Additionally, by analyzing the customs and social standing of patuas in the context of their religious thought, we aim to uncover new dimensions in this field of research. Patua-Sangit, Gurusadaya Datta. Bangla Lokosahittya, Ashutash Bhattacharya. Banglar Chitrakala, Ashok Bhattacharya. Banglar Chitrakala Maddhajug Theke Kalighat, Anjan Sen. Banglar Pat, Bishwandha Nanda. Bangio Lokosonskriticosh, Barun Kumar Chakraborty. Lokosonskriti Biswacosh, Dulal Chowdhury and Bangladesher Patachitra, Patagitir Patabhumite Nikhilchandra Daser Patashilpe Samaj Bikshan, Dr. Chittaranjan Maiti. Gazir Pat, Ashraf Siddiqi etc. In these books, there are discussions on Gajir Pat and Gaji Pir’s story, have been the conversation in these books. The religious views of Gajir story’s artists have not been discussed. That is why I think there is a need to discuss the matter in detail. Jagannath University Journal of Arts, v-15, i-01, 2025:p39-53